Polyphenolic compounds of Euphorbia umbellata (Pax) Bruyns (Euphorbiaceae) improved endothelial dysfunction through arginase inhibition. (22nd December 2020) - Minozzo, Bruno Rodrigo; de Andrade, Evelyn Assis; Vellosa, José Carlos Rebuglio; Lipinski, Leandro Cavalcante; Fernandes, Daniel; Nardi, Geisson Marcos; Rodrigues, Ricardo Pereira; Kitagawa, Rodrigo Rezende; Girard, Corine; Demougeot, Céline; Beltrame, Flávio Luís
Abstract : Euphorbia umbellata is used for its anti‐inflammatory properties; however, there are limited data available regarding its effects on vascular function. Its bark is rich in polyphenolic compounds, which potentially improve endothelial dysfunction (ED). This study proposes to investigate the effects of E . umbellata bark extracts and its polyphenolic compounds on arginase (ARG) activity and nitric oxide (NO)‐related targets. Chromatographic procedures were used for the chemical characterisation of the extracts. Furthermore, in silico (molecular docking), in vitro (ARG inhibition), in vivo (streptozotocin‐induced hyperglycemia model), and ex vivo (l ‐arginine metabolism, vascular reactivity, western blot, and biochemical) techniques were carried out. Quercetin, gallic acid, and ellagic acid were identified in the extracts. In silico screening predicted that gallic acid and quercetin would have the most promising interactions with ARG ‐identified cavities. This was confirmed in vitro as both compounds had a direct inhibitory effect on ARG, as was the case regarding the extracts. Oral treatment preserved endothelium‐dependent vasodilation through ARG inhibition together with an increase in l ‐arginine bioavailability and endothelial NO synthase expression. Biochemical parameters determined the lack of toxicity for sub‐chronic treatment. E . umbellata bark extracts and its compounds can contribute to ED treatment, at least partly, through the inhibition of vascular ARG.